News and Frontier Consciousness in the Late Roman Empire - Graham, Mark W. (University of Michigan Press, 2006)
Prior to the third century A.D., two broad Roman conceptions of frontiers proliferated and competed: an imperial ideology of rule without limit coexisted with very real and pragmatic attempts to define and defend imperial frontiers. But from about A.D. 250-500, there was a basic shift in mentality, as news from and about frontiers began to portray a more defined Roman world-a world with limits-allowing a new understanding of frontiers as territorial and not just as divisions of people. This concept, previously unknown in the ancient world, brought with it a new consciousness, which soon spread to cosmology, geography, myth, sacred texts, and prophecy. The "frontier consciousness" produced a unified sense of Roman identity that transcended local identities and social boundaries throughout the later Empire. Approaching Roman frontiers with the aid of media studies as well as anthropological and sociological methodologies, Mark W. Graham chronicles and documents this significant transition in ancient thought, which coincided with, but was not necessarily dependent on, the Christianization of the Roman world.